2014
DOI: 10.1007/978-3-319-08894-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Astrocytes in Delayed Neuronal Death: GLT-1 and its Novel Regulation by MicroRNAs

Abstract: Astrocytes have been shown to protect neurons from delayed neuronal death and increase their survival in cerebral ischemia. One of the main mechanisms of astrocyte protection is rapid removal of excess glutamate from synaptic sites by astrocytic plasma membrane glutamate transporters such as GLT-1/EAAT-2, reducing excitotoxicity. Astrocytic mitochondrial function is essential for normal GLT-1 function. Manipulating astrocytic mitochondrial and GLT-1 function is thus an important strategy to enhance neuronal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 101 publications
0
23
0
Order By: Relevance
“…; for review, see Ouyang et al . ). Disruption of the BBB reduces GLT‐1 expression, reduces glutamate uptake, and results in spontaneous epileptic seizures in vivo (David et al .…”
Section: Discussionmentioning
confidence: 97%
“…; for review, see Ouyang et al . ). Disruption of the BBB reduces GLT‐1 expression, reduces glutamate uptake, and results in spontaneous epileptic seizures in vivo (David et al .…”
Section: Discussionmentioning
confidence: 97%
“…Pyramidal neurons in the cornu ammonis 1 (CA1) region of the hippocampus are selectively sensitive to ischemia, dying in the days following reperfusion. However neurons in the adjacent dentate gyrus (DG) have a relatively higher ischemic resistance and survive (for review, Ouyang et al , 2014). Delayed neuronal death in the CA1 occurs secondary to disruption in mitochondrial function (Owens et al , 2015), inducing release of cytochrome c and other pro-apoptotic factors into the cytoplasm (Ouyang et al , 1999; Niizuma et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes, the most abundant cell type in the brain, play many key roles supporting normal neuronal functioning, including preserving ionic and acid-base balance, modulating neurotransmission, and maintaining neuronal energy stores (Clarke & Barres, 2013; Barreto et al , 2011). Critically, astrocyte homeostasis is tightly coupled to neuronal cell fate following ischemic injury (Nedergaard & Dirnagl, 2005; Barreto et al , 2011; Ouyang et al , 2014). We have previously observed that both neurons and astrocytes isolated from different brain regions show differential sensitivity to injuries (Xu et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…GLT-1 is so named due to its main distribution on glial cells. GLT-1 can remove excess glutamate and reduce excitotoxicity (7). Over 90% of glutamate uptake is carried out by GLT-1 in the adult forebrain (6).…”
Section: Introductionmentioning
confidence: 99%